Effectiveness of Nursing Interventions in Reducing Maternal Mortality in Resource-Limited Settings: A Systematic Review and Meta-Analysis - Kaur, Jasneet; Upendra, Sheela (Investigación y Educación en Enfermería, 2025)
Objective. To assess the effectiveness of nurse-led or nurse-integrated interventions in improving maternal health outcomes, particularly antenatal care (ANC) attendance, in resource-constrained settings. Methods. A systematic review and meta-analysis were conducted following PRISMA guidelines. Databases including PubMed, Scopus, CINAHL and Web of Science were searched for studies evaluating the impact of nursing interventions on maternal health outcomes. Risk of bias was assessed using the Cochrane RoB 2 tool and Newcastle-Ottawa Scale. A random-effects meta-analysis was performed for studies reporting ANC attendance (4 and more visits). (PROSPERO CRD420251067253). Results. Of the 1038 records identified, 11 studies met the inclusion criteria, and 3 were eligible for meta-analysis. The pooled Odds Ratio for ANC attendance was 1.48 (95% CI = 1.06–2.08), indicating a statistically significant improvement. For facility use at birth, results also showed positive effects (OR=1.49, 95% CI = 1.21–1.77). Mortality-related outcomes showed a midwife-delivered postpartum hemorrhage bundle reduced a composite outcome including severe hemorrhage and death (RR = 0.40, 95% CI = 0.32–0.50) Narrative synthesis of other outcomes such as skilled birth attendance and maternal mortality also suggested a positive impact of nurse-led interventions. Conclusion. Nurse-led and nurse-integrated maternal health interventions significantly improve ANC utilization in low-resource settings. Policymakers should consider scaling these models as part of broader maternal health strategies